A stepped pore anodic aluminum oxide carrier, prepared catalyst and application thereof

By designing a stepped porous anodized aluminum carrier, the internal diffusion problem of the integral methanol steam reforming catalyst was solved, the activity and reaction efficiency of the catalyst were improved, and the preparation process was simplified.

CN118767903BActive Publication Date: 2025-01-21EAST CHINA UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410871360.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-01-21
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

The internal diffusion problem of the integral methanol water vapor reforming catalyst affects the chemical reaction rate, and it is difficult for the prior art to optimize the pore structure to improve activity, and there is an increase in molding cost and technical difficulty.

Method used

By designing the pore structure of the catalyst carrier, a stepped pore anodic aluminum carrier is used, and oxalic acid, malonic acid and tartaric acid solutions are used for step-by-step anodization to form a pore structure with appropriate internal diffusion resistance.

Benefits of technology

It improves the activity of the catalyst, increases the probability of collision between reactants and active sites, promotes the occurrence of deep reactions, solves the problem of internal diffusion, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118767903B_ABST
    Figure CN118767903B_ABST
Patent Text Reader

Abstract

The present invention discloses a stepped pore anodized aluminum carrier, a prepared catalyst and its application, belonging to the field of catalysts. The present invention sequentially anodizes an aluminum substrate in different solutions, and then obtains the stepped pore anodized aluminum carrier after roasting; the different solutions are oxalic acid solution, malonic acid solution and tartaric acid solution. The present invention designs the pore structure of the catalyst carrier so that the catalyst has a suitable internal diffusion resistance, increases the collision probability of reactants and active sites, promotes the occurrence of deep reactions, improves the activity of the monolithic methanol steam reforming catalyst prepared by the anodized aluminum carrier, and solves the internal diffusion problem in the practical application of the monolithic mesh catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a stepped pore anodic aluminum oxide carrier, a prepared catalyst and applications thereof. Background Art

[0002] Achieving a balance between economic development and environmental protection is a daunting challenge facing the world today. In most cases, the use of energy brings about environmental damage, especially fossil fuels such as coal and crude oil, whose combustion greatly increases the carbon content in the atmosphere and aggravates climate change. In 2019, the International Energy Agency pointed out in a report that for every 1% increase in global economic output, annual carbon dioxide emissions will increase by 0.5%. Therefore, in the past few decades, the use of non-carbon renewable energy such as solar energy, wind energy, geothermal energy, tidal energy and hydrogen energy has received widespread attention. However, except for hydrogen energy, the above renewable energy sources have problems of intermittent or insufficient supply and lack the reliability required for power generation. Hydrogen not only reduces the emission of air pollutants like the above renewable energy sources, but also has an efficiency that is even higher than that of gasoline. At the same time, the use of hydrogen energy has certain economic benefits. It is estimated that by 2050, hydrogen will become a key energy source, accounting for 18% of global energy demand. However, under current technology, the storage and transportation of H2 have certain safety issues. The methanol steam reforming technology can be applied to distributed equipment through on-site hydrogen production or coupling with high-temperature proton exchange membrane fuel cells to overcome the storage and transportation problems of hydrogen. Compared with traditional granular catalysts, monolithic catalysts have the advantages of low pressure drop, efficient mass and heat transfer, high flux, easy molding, and easy transportation, and are more suitable for distributed hydrogen production equipment. The internal diffusion problem of monolithic catalysts is an important factor affecting the chemical reaction rate. Changing the internal diffusion resistance of the catalyst requires optimizing the pore structure, which increases the molding cost and technical difficulty. Therefore, in the methanol steam reforming technology, developing a methanol steam reforming catalyst carrier with a simple process and suitable internal diffusion resistance is one of the key issues.

[0003] CN 114192151 A discloses a methanol steam reforming hydrogen production catalyst synthesized by PCVD method. The preparation method comprises: adjusting the pH value of a mixed solution of copper nitrate, aluminum nitrate and zinc nitrate metal salts to obtain a metal salt precipitate; drying and crushing the metal salt precipitate to use as a catalyst precursor; reducing a lanthanide metal precursor to a lanthanum metal element, using a chemical vapor deposition process to deposit it on the surface of the catalyst precursor and then performing an oxidation treatment. The above catalyst can reduce the CO content in the product by using it to produce hydrogen from methanol reforming.

[0004] CN 112827483 A discloses a preparation method and application of a hydrogen production catalyst prepared by a hydrothermal method and a coprecipitation method, wherein the catalyst comprises five elements: zinc, aluminum, lanthanum, copper and oxygen, wherein the mass proportions of the above elements are 40-50%, 12-25%, 2-5%, 1-5%, respectively, and the rest is oxygen. The hydrogen yield at 300°C can reach the level of an industrial catalyst at 450°C, and the concentrations of carbon monoxide and dimethyl ether are basically controlled at a level similar to that of an industrial catalyst.

[0005] CN 109603834 A discloses a catalyst for hydrogen production by steam reforming of methanol, the components of which include Cu, La2O3 and ZrO2, wherein the molar percentage of La is 1-5%, the molar percentage of Cu is 5-40%, and the molar percentage of Zr is 55-94%. The preparation method of the catalyst includes: firstly, a mixed solution of copper nitrate, lanthanum nitrate and zirconium oxychloride and a sodium carbonate solution are co-precipitated to form a sol, further aged, evaporated to form a gel, dried and roasted, and then roasted again after being treated with dilute nitric acid. The Cu / La2O3 / ZrO2 catalyst is treated with acid to remove the copper component that has a weak interaction with the carrier, thereby fully exposing the copper-zirconium interface and increasing the stability of the catalyst.

[0006] CN 108671927 A discloses a composite catalyst for hydrogen production by methanol steam reforming prepared by a high-energy ball milling method, wherein the catalyst comprises 30-70wt% of a perovskite-type composite metal oxide, 1.5-10.5wt% of ZnO, 1.5-14wt% of Al2O3 and the remainder of CuO. The general structural formula of the perovskite-type composite metal oxide is A2BO4, wherein A is a rare earth metal element and B is a transition metal element. The catalyst has high activity in a wide temperature range.

[0007] The above catalysts all use metal additives such as zinc oxide and lanthanum oxide to improve the activity or stability of copper-based catalysts in methanol steam reforming, but they are all granular catalysts and require a long high-temperature pre-activation process with hydrogen to start the process, making them difficult to use in distributed hydrogen production equipment.

[0008] CN 112588279 A discloses a preparation method of a catalyst for hydrogen production by methanol steam reforming, and its products and applications. The patent significantly improves the stability of the catalyst by placing the catalyst carrier in an iron nitrate solution for iron ion loading before copper loading, and magnesium loading can reduce the acidity of the carrier, thereby improving the catalytic efficiency of copper for hydrogen production by methanol reforming. The anodic oxidation carrier used in the patent has a single pore structure and poor catalytic activity under medium and low temperature conditions.

[0009] CN 106140169 A discloses a structured carrier formed by forming a thin film of aluminum oxide with a nanoporous structure on the surface of plate-shaped or mesh-shaped aluminum by an anodic oxidation method, and applying the structured carrier to a dimethyl ether steam reforming catalyst. In this patent, only oxalic acid is used to anodize aluminum. The pores obtained by oxalic acid anodization are small and have a large internal diffusion resistance, that is, the effective active layer of the catalyst is thin, and the active components deep in the catalyst pores are not fully utilized. Summary of the invention

[0010] In order to solve the internal diffusion problem of the integral methanol steam reforming catalyst, the present invention proposes a stepped pore anodized aluminum carrier, a prepared catalyst and its application. The present invention designs the pore structure of the catalyst carrier so that the catalyst has a suitable internal diffusion resistance, increases the collision probability between the reactants and the active sites, promotes the occurrence of deep reactions, improves the activity of the integral methanol steam reforming catalyst prepared by the anodized aluminum carrier, and solves the internal diffusion problem in the actual application of the integral mesh catalyst.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] One of the technical solutions of the present invention:

[0013] A method for preparing a stepped pore anodic aluminum oxide carrier comprises the following steps:

[0014] Anodizing the aluminum substrate in different solutions in turn, and then calcining it to obtain the stepped pore anodized aluminum carrier;

[0015] The different solutions are oxalic acid solution, malonic acid solution and tartaric acid solution in sequence.

[0016] Preferably, the aluminum substrate is pretreated before use, and the pretreatment method is: the aluminum substrate is treated with 5-15wt% sodium hydroxide solution and 5-15wt% nitric acid solution for 1-5 minutes respectively.

[0017] Preferably, the aluminum substrate is an aluminum mesh. The support obtained by calcining the anodized aluminum substrate is porous anodized aluminum AAO.

[0018] Preferably, the anodizing of the aluminum substrate in different solutions in sequence is: using oxalic acid solution, malonic acid solution and tartaric acid solution as electrolytes in sequence to perform a three-step anodizing treatment on the aluminum substrate.

[0019] Preferably, when an oxalic acid solution is used as the electrolyte to perform anodizing treatment on the aluminum substrate, it is called the first anodizing treatment, and the temperature of the first anodizing treatment is 15-25° C., the voltage is 10-30V, the time is 4-12h, and the concentration of the oxalic acid solution is 0.2-0.6mol / L;

[0020] When the product after the first step of anodizing treatment is anodized by using malonic acid solution as the electrolyte, it is called the second step of anodizing treatment. The temperature of the second step of anodizing treatment is 15-25°C, the voltage is 30-50V, the time is 4-12h, and the concentration of the malonic acid solution is 1.5-1.9mol / L;

[0021] When tartaric acid solution is used as the electrolyte to anodize the product after the second step anodizing treatment, it is called the third step anodizing treatment. The temperature of the third step anodizing treatment is 15-25°C, the voltage is 50-70V, the time is 4-12h, and the concentration of the tartaric acid solution is 0.8-1.2mol / L.

[0022] More preferably, the order of the electrolytes during anodization is: (1) oxalic acid solution, (2) malonic acid solution, and (3) tartaric acid solution. The concentration of the oxalic acid solution is 0.3 mol / L, the temperature is 20°C, the voltage is 20V, and the time is 12h; the concentration of the malonic acid solution is 1.7 mol / L, the temperature is 15°C, the voltage is 40V, and the time is 12h; the concentration of the tartaric acid solution is 1 mol / L, the temperature is 15°C, the voltage is 60V, and the time is 12h.

[0023] Preferably, the calcination temperature is 350-550° C. and the time is 1-3 h, more preferably the calcination temperature is 350° C. and the time is 1 h.

[0024] The structure of anodized aluminum depends largely on the anodizing conditions. The present invention effectively regulates the size and density of the pores by controlling the type of acid in the anodizing electrolyte. Specifically, the present invention obtains a carrier with a gradually increasing pore structure by anodizing an aluminum substrate in electrolytes of oxalic acid solution, tartaric acid solution, and malonic acid solution in sequence. The catalyst prepared using a carrier with this structure not only improves the activity of the catalyst, but also eliminates the need to cut the catalyst into pieces during use to reduce internal diffusion resistance, making the flexible mesh catalyst more suitable for use in distributed equipment. At 12000mL / (g cat h), the methanol conversion rate of 1g of CuLa / AAO-cao bing wine catalyst at 325℃ was 93.7%, and the H2 yield was 89.4%. The development of stepped pore anodic aluminum oxide methanol steam reforming catalyst provides a feasible solution for on-site hydrogen production.

[0025] The second technical solution of the present invention:

[0026] The present invention also provides a stepped pore anodic aluminum oxide carrier prepared by the above preparation method.

[0027] The third technical solution of the present invention:

[0028] The present invention also provides a catalyst, the carrier of which is the stepped pore anodic aluminum oxide carrier.

[0029] The fourth technical solution of the present invention:

[0030] The present invention also provides a method for preparing the catalyst, comprising the following steps: sequentially loading an auxiliary metal compound and a copper compound on the stepped pore anodized aluminum carrier to obtain the catalyst.

[0031] Preferably, the method for loading the auxiliary metal compound comprises: heating zinc nitrate, lanthanum nitrate or cerium nitrate at 90-98°C in water to liquid state, placing the stepped pore anodized aluminum support in the above solution, immersing at 90-98°C for 1-4h, drying naturally and then calcining at 400-550°C for 4h;

[0032] The method for loading copper compounds comprises: placing the calcined product in a copper nitrate solution with a concentration of 1.5 mol / L, immersing at 25° C. for 10-20 hours, and calcining at 400-550° C. for 4 hours after natural drying.

[0033] More preferably, the stepped pore anodized aluminum carrier is immersed in the solution at a temperature of 95°C, an immersion time of 2 hours, and a calcination temperature of 500°C.

[0034] More preferably, the impregnation time of the supported copper compound is 20 hours and the calcination temperature is 500°C.

[0035] More preferably, the copper compound is a mixture of cupric oxide and cuprous oxide.

[0036] More preferably, the loading amount of the promoter metal compound in the catalyst is 1-3 wt %, and the loading amount of copper is 10-15 wt %.

[0037] The fifth technical solution of the present invention:

[0038] The present invention also provides the use of the catalyst in methanol steam reforming. When the catalyst of the present invention is used, it does not need to be pre-activated with hydrogen, and can achieve rapid startup in the methanol steam reforming reaction and efficiently produce hydrogen.

[0039] The present invention performs step-by-step anodic oxidation in three acids, so that the pore structure of the monolithic mesh catalyst is a stepped structure, has a suitable internal diffusion resistance, and is more suitable for methanol steam reforming reaction. In addition, the pore structure in the catalyst of the present invention is richer, which improves the internal diffusion of the catalyst and enhances the catalytic activity of the catalyst under medium and low temperature conditions.

[0040] Compared with the prior art, the present invention has the following advantages and technical effects:

[0041] The present invention designs the pore structure of the catalyst carrier so that the catalyst has a suitable internal diffusion resistance. The deep tartaric acid macropores are used to accommodate more reactants and intermediates, and the smaller oxalic acid layer pores on the outside are used to restrict the unreacted substances from leaving the pores, thereby increasing the probability of collision with the active sites, promoting the occurrence of deep reactions, and improving the activity of the methanol steam reforming catalyst prepared by the anodized aluminum carrier.

[0042] The catalyst preparation process disclosed in the present invention is simple and can be industrially mass-produced. Moreover, the catalyst does not need to be pre-activated with hydrogen, and can be quickly started in the methanol steam reforming reaction and efficiently produce hydrogen. cat ·h), the methanol conversion rate of 1g of CuLa / AAO-cao-bing wine catalyst was 93.7% and the H2 yield was 89.4% when reacted at 325℃. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0044] Figure 1 This is a flow chart of preparing the stepped pore anodized aluminum and its bimetallic catalyst in Example 1 of the present invention;

[0045] Figure 2 (a), (b), (c) and (d) are cross-sectional SEM images of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively;

[0046] Figure 3 N2 adsorption-desorption curves (a) and pore size distribution diagrams (b) of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;

[0047] Figure 4 The methanol conversion results of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at 225-325° C. are shown;

[0048] Figure 5The hydrogen yield results of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at 225-325° C. are shown;

[0049] Figure 6 The dimethyl ether selectivity result diagram of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at 225-325°C;

[0050] Figure 7 This is a graph showing the methanol conversion rate of the catalyst prepared in Example 2 at 225-325°C;

[0051] Figure 8 This is a graph showing the methanol conversion rate of the catalyst prepared in Example 3 at 225-325°C. DETAILED DESCRIPTION

[0052] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0053] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0054] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0055] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0056] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0057] All raw materials used in the embodiments of the present invention are commercially available.

[0058] The technical solution of the present invention is further illustrated by the following embodiments.

[0059] Example 1

[0060] The preparation method of the stepped pore anodized aluminum carrier is as follows: the aluminum mesh is pre-treated with 10wt% sodium hydroxide solution and 10wt% nitric acid solution for 4min and 2min respectively, placed in an anodizing tank, and placed in a 0.3mol / L oxalic acid solution with a current voltage of 20V at 20°C for the first step of anodization, and the first step of anodization time is 12h. After rinsing with deionized water and drying naturally, the second step of anodization is carried out at 15°C, the solution is replaced with 1.7mol / L malonic acid solution, and anodization is carried out at 40V for 12h. After rinsing with deionized water and drying naturally, the third step of anodization is carried out at 15°C, the solution is replaced with 1.0mol / L tartaric acid solution, and anodization is carried out at 60V for 12h. After rinsing with deionized water and drying naturally, it is calcined at 350°C for 1h to obtain the AAO-grass third wine carrier.

[0061] Lanthanum nitrate was heated in water at 95°C to become liquid to obtain a saturated solution of lanthanum nitrate. The AAO-grass third wine carrier was placed in the saturated solution of lanthanum nitrate and immersed at 95°C for 2 hours. After the surface was dried, it was naturally dried and then calcined at 500°C for 4 hours to obtain a catalyst loaded with lanthanum compound. The catalyst loaded with lanthanum compound was placed in a copper nitrate solution with a concentration of 1.5 mol / L, immersed at 25°C for 20 hours, naturally dried and then calcined at 500°C for 4 hours to obtain a CuLa / AAO-grass third wine catalyst. 1g of the CuLa / AAO-grass third wine catalyst was cut into 9mm small discs, threaded together with iron wire, placed in the center of a stainless steel fixed bed tubular reactor, and subjected to methanol-water vapor reaction under atmospheric pressure. The catalyst was not pre-reduced. The methanol aqueous solution (n 水 :n 甲醇 =2:1) ​​was pumped into a 150°C vaporizer, then mixed with nitrogen (40 mL / min) as a balance gas, and finally entered a tubular fixed bed reactor. The catalyst was self-activated at 225°C and reacted in the reaction temperature range of 225°C-325°C, with a gas hourly space velocity of 12000 mL / (g cat h). The gaseous products were analyzed by an online gas chromatograph equipped with a flame ionization detector and a thermal conductivity detector.

[0062] Example 2

[0063] The aluminum mesh was pre-treated with 5wt% sodium hydroxide solution and 5wt% nitric acid solution for 1min and 5min respectively, and then placed in an anodizing tank, and placed in a 0.4mol / L oxalic acid solution with a current voltage of 10V at 18°C ​​for the first step of anodization, and the first step of anodization time was 10h. After rinsing with deionized water and drying naturally, the second step of anodization was carried out at 18°C, and the solution was replaced with 1.5mol / L malonic acid solution, and anodization was carried out at 30V for 10h. After rinsing with deionized water and drying naturally, the third step of anodization was carried out at 18°C, and the solution was replaced with 0.8mol / L tartaric acid solution, and anodization was carried out at 50V for 10h. After rinsing with deionized water and drying naturally, it was calcined at 450°C for 2h to obtain the AAO-grass third wine carrier. Zinc nitrate was heated in water at 90°C to become liquid to obtain a saturated zinc nitrate solution, and the AAO-grass butyl wine carrier was placed in the saturated zinc nitrate solution and immersed at 90°C for 4 hours. After the surface was dried, it was naturally dried and then calcined at 400°C for 4 hours to obtain a catalyst loaded with zinc compound. The catalyst loaded with zinc compound was placed in a copper nitrate solution with a concentration of 1.5 mol / L, immersed at 25°C for 10 hours, naturally dried and then calcined at 400°C for 4 hours to obtain a CuZn / AAO-grass butyl wine catalyst.

[0064] Example 3

[0065] The aluminum mesh was pre-treated with 15wt% sodium hydroxide solution and 15wt% nitric acid solution for 5min and 2min respectively, and then placed in an anodizing tank and placed in a 0.4mol / L oxalic acid solution with a current voltage of 30V at 24°C for the first step of anodization. The first step of anodization time was 4h. After rinsing with deionized water and drying naturally, the second step of anodization was carried out at 24°C, and the solution was replaced with 1.9mol / L malonic acid solution, and anodization was carried out at 50V for 4h. After rinsing with deionized water and drying naturally, the third step of anodization was carried out at 24°C, and the solution was replaced with 1.2mol / L tartaric acid solution, and anodization was carried out at 70V for 12h. After rinsing with deionized water and drying naturally, it was calcined at 550°C for 3h to obtain the AAO-grass third wine carrier. Cerium nitrate was heated in water at 98°C to become liquid to obtain a saturated cerium nitrate solution, and the AAO-grass nitrate carrier was placed in the saturated cerium nitrate solution and immersed at 98°C for 1 hour. After the surface was dried by absorbing, it was naturally dried and then calcined at 550°C for 4 hours to obtain a catalyst loaded with cerium compound. The catalyst loaded with cerium compound was placed in a copper nitrate solution with a concentration of 1.5 mol / L, immersed at 25°C for 20 hours, naturally dried and then calcined at 550°C for 4 hours to obtain a CuCe / AAO-grass nitrate catalyst.

[0066] Comparative Example 1

[0067] Compared with Example 1, the preparation conditions of the AAO carrier are different. This comparative example is the carrier preparation conditions conventionally used in the AAO carrier laboratory (that is, the AAO carrier in this comparative example is anodized aluminum obtained by oxidizing the aluminum mesh using only oxalic acid solution). Specifically, at 20°C, the aluminum mesh is placed in a current voltage of 30A / m 2 The CuLa / AAO catalyst was obtained by calcining and loading the active species under the same conditions as in Example 1.

[0068] Comparative Example 2

[0069] Compared with Example 1, the preparation conditions of the AAO carrier are different, and the other conditions are the same as those in Example 1. The preparation method of the AAO carrier is as follows: the first step is to place it in a 1.0 mol / L tartaric acid solution with a current voltage of 60V at 15°C for the first step of anodization for 12 hours. After rinsing with deionized water and drying naturally, the second step of anodization is carried out, and the solution is replaced with a 1.7 mol / L malonic acid solution, and anodization is carried out at 40V for 12 hours. After rinsing with deionized water and drying naturally, the third step of anodization is carried out, and the solution is replaced with a 0.3 mol / L oxalic acid solution, and anodization is carried out at 20V for 12 hours to obtain a CuLa / AAO-tartrate catalyst.

[0070] Comparative Example 3

[0071] Compared with Example 1, the preparation conditions of the AAO carrier are different, and the other conditions are the same as those in Example 1. The preparation method of the AAO carrier is as follows: the first step is to place it in a 1.0 mol / L tartaric acid solution with a current voltage of 60V at 15°C for anodization for 6 hours. Then the second step of anodization is carried out, the solution is replaced with a 0.3 mol / L oxalic acid solution, and anodization is carried out at 20V for 6 hours. Then the third step of anodization is carried out, the solution is replaced with a 1.0 mol / L tartaric acid solution, and anodization is carried out at 60V for 6 hours. Then the fourth step of anodization is carried out, the solution is replaced with a 0.3 mol / L oxalic acid solution, and anodization is carried out at 20V for 6 hours. Then the fifth step of anodization is carried out, the solution is replaced with a 1.0 mol / L tartaric acid solution, and anodization is carried out at 60V for 6 hours. Finally, the sixth step of anodization is carried out, the solution is replaced with a 0.3 mol / L oxalic acid solution, and anodization is carried out at 20V for 6 hours. Before each anodic oxidation, the sample was rinsed with deionized water and dried naturally to obtain a CuLa / AAO-aluminum intermittent catalyst.

[0072] Figure 1 This is a flow chart of preparing the stepped pore anodized aluminum and its bimetallic catalyst in Example 1 of the present invention.

[0073] Figure 2(a), (b), (c) and (d) are cross-sectional SEM images of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. It can be seen that the pores of the anodized aluminum in the best Example 1 are three-level pores, the outermost section is a smaller pore generated in the oxalic acid solution, the innermost section is a larger pore generated in the tartaric acid solution, and the middle section is a pore generated in the malonic acid solution, the size of which is between tartaric acid and oxalic acid. Comparative Example 1 is an ordinary straight pore with no step change. Comparative Example 2 is opposite to Example 1, the outermost section is a larger pore generated in the tartaric acid solution, and the innermost section is a smaller pore generated in the oxalic acid solution. Comparative Example 3 is anodized alternately in two solutions, the small pores grow from the macroporous structure, and the pores are pine-like structures.

[0074] Figure 3 The N2 adsorption-desorption curves (a) and pore size distribution diagrams (b) of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 show that all catalysts exhibit type IV adsorption-desorption isotherms related to capillary condensation. The difference is that the N2 adsorption-desorption isotherm of CuLa / AAO exhibits a H2(b) type hysteresis loop, which is a typical mesoporous material. The CuLa catalysts prepared by the three variable pore AAO carriers exhibit an H4 type hysteresis loop and no obvious saturated adsorption platform, indicating that the pore structure is irregular, further proving its stepped pore structure.

[0075] Figure 4 The methanol conversion results of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at 225-325°C show that the CuLa / AAO-Cao Bing Wine catalyst has a significantly higher methanol conversion rate than other step channel catalysts and straight channel catalysts. The methanol conversion rate of the CuLa / AAO-Cao Bing Wine catalyst at 325°C is 93.7%, while the methanol conversion rates of the CuLa / AAO catalyst, CuLa / AAO-Cao Bing Wine and CuLa / AAO-Cao Bing Wine intermittent catalyst at this temperature are 85.1, 53.7 and 39.2%, respectively.

[0076] Figure 5The hydrogen yield results of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at 225-325°C show that the activity of the CuLa / AAO-Cao Bing Wine catalyst is significantly higher than that of CuLa / AAO at 250-325°C, and the H2 yield is 89.4% at 325°C, while the H2 yield of the CuLa / AAO catalyst at this temperature is only 67.8%. The activity of the CuLa / AAO-Cao Bing Wine and CuLa / AAO-Cao Jing intermittent catalysts is slightly lower than that of the CuLa / AAO catalyst, among which the CuLa / AAO-Cao Jing intermittent catalyst with the most irregular pore structure has the lowest activity, and the H2 yield at 325°C is only 47.6%.

[0077] Figure 6 The dimethyl ether selectivity result diagram of the catalysts prepared for Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at 225-325°C shows that with the increase of reaction temperature, the dimethyl ether selectivity of the CuLa / AAO-wine-grass catalyst increases significantly and gradually, the dimethyl ether selectivity of the CuLa / AAO-wine-grass intermittent catalyst increases first and then decreases, and the dimethyl ether selectivity of the CuLa / AAO-grass-grass catalyst decreases gradually. This phenomenon shows that different pore structures can affect the selectivity of the reaction products. The possible reason is that the tartaric acid macroporous layer in the hierarchical pore structure promotes the entry and exit of reactants and products, while the oxalic acid microporous layer restricts their entry and exit. For the CuLa / AAO-wine-grass catalyst, with the increase of reaction temperature, the reactants enter and leave the pores at the same time, which promotes the non-deep reaction and increases the dimethyl ether selectivity. For the CuLa / AAO-grass-grass-grass catalyst, the rate at which the reactants enter and leave the pores is limited, which promotes the occurrence of deep reactions, so the dimethyl ether selectivity gradually decreases.

[0078] Figure 7 The methanol conversion rate of the catalyst prepared in Example 2 at 225-325°C is shown in the figure. It can be seen that the methanol conversion rate of the CuZn / AAO-Cao Bing wine catalyst at 325°C is 68.4%, and its MSR activity is better than that of the CuLa / AAO-Cao Bing wine and CuLa / AAO-Cao Bing wine intermittent catalysts. However, since the voltage is 10V during oxidation in oxalic acid solution, the rate of generating the alumina layer is low, and the final alumina layer is significantly thinner, and the limiting effect on reactants and products is weaker, and its methanol conversion rate is lower than that of the CuLa / AAO-Cao Bing wine catalyst.

[0079] Figure 8The methanol conversion rate of the catalyst prepared in Example 3 at 225-325°C is shown in Table 1. It can be seen that the methanol conversion rate of the CuCe / AAO-Cao Bing wine catalyst at 325°C is 97.8%, and the methanol conversion rate at all temperatures is close to that of the CuLa / AAO-Cao Bing wine catalyst. Table 1 shows the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in a network (internal diffusion is not excluded, E v,a ) and in granular form (internal diffusion has been excluded, E int,a ) is used to calculate the activation energy barrier for the reaction and the Schiller modulus calculated from the activation energy barrier.

[0080] Table 1 Reaction-diffusion kinetic parameters of catalysts with different pore structures

[0081]

[0082] The Schiller modulus, i.e., the order of the internal diffusion resistance is CuLa / AAO>CuLa / AAO-Cao Bing Wine>CuLa / AAO-Cao Bing Wine Intermittent>CuLa / AAO-Cao Bing Wine Grass. CuLa / AAO-Cao Bing Wine Intermittent and CuLa / AAO-Cao Bing Wine Grass have smaller internal diffusion resistance due to the large pores in the outer layer, especially CuLa / AAO-Cao Bing Wine Grass with inverted trapezoidal pores. CuLa / AAO-Cao Bing Wine with a macroporous structure deep in the pores has a smaller internal diffusion resistance than CuLa / AAO, but has a larger internal diffusion resistance than the other two catalysts with macroporous structures on the outside. Combined with the catalyst activity, it can be inferred that the deep pores of CuLa / AAO-Cao Bing Wine can accommodate more reactants and intermediates, and the smaller pores on the outside can limit the unreacted substances from leaving the pores, increasing the probability of collision with the active sites, so it has the best activity. CuLa / AAO with the largest internal diffusion resistance limits the entry and exit of reactants and products, thereby reducing its catalytic efficiency. The CuLa / AAO-Cao Bing Jiu pores with smaller internal diffusion resistance also promote the ingress and egress of reactants, but cannot promote their collision with active sites. Therefore, the CuLa-AAO / Cao Bing Jiu pores promote the reaction through appropriate internal diffusion resistance.

[0083] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a stepped pore anodized aluminum support, characterized in that: The following steps are involved: Anodizing the aluminum substrate in different solutions in turn, and then calcining it to obtain the stepped pore anodized aluminum carrier; The different solutions are oxalic acid solution, malonic acid solution and tartaric acid solution in sequence; When the aluminum substrate is anodized using oxalic acid solution as the electrolyte, it is called the first anodizing treatment. The temperature of the first anodizing treatment is 15-25° C., the voltage is 10-30V, the time is 4-12h, and the concentration of the oxalic acid solution is 0.2-0.6mol / L. When the product after the first step of anodizing treatment is anodized by using malonic acid solution as the electrolyte, it is called the second step of anodizing treatment. The temperature of the second step of anodizing treatment is 15-25°C, the voltage is 30-50V, the time is 4-12h, and the concentration of the malonic acid solution is 1.5-1.9mol / L; When tartaric acid solution is used as the electrolyte to anodize the product after the second step anodizing treatment, it is called the third step anodizing treatment. The temperature of the third step anodizing treatment is 15-25°C, the voltage is 50-70V, the time is 4-12h, and the concentration of the tartaric acid solution is 0.8-1.2mol / L.

2. The method for preparing a stepped pore anodized aluminum carrier according to claim 1, characterized in that: The aluminum substrate is pretreated before use, and the pretreatment method is: the aluminum substrate is treated with 5-15wt% sodium hydroxide solution and 5-15wt% nitric acid solution for 1-5 minutes respectively.

3. The method for preparing a stepped pore anodized aluminum carrier according to claim 1, characterized in that: The step of anodizing the aluminum substrate in different solutions in sequence comprises: using oxalic acid solution, malonic acid solution and tartaric acid solution as electrolytes in sequence to perform a three-step anodizing treatment on the aluminum substrate.

4. The method for preparing a stepped pore anodized aluminum carrier according to claim 1, characterized in that: The calcination temperature is 350-550° C. and the calcination time is 1-3 hours.

5. A stepped pore anodized aluminum carrier, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 4.

6. A catalyst, characterized in that The carrier is the stepped pore anodized aluminum carrier as described in claim 1.

7. A method for preparing the catalyst according to claim 6, characterized in that: The following steps are involved: The catalyst is obtained by sequentially loading an auxiliary metal compound and a copper compound on the stepped pore anodized aluminum carrier.

8. The method for preparing the catalyst according to claim 7, characterized in that: The method for loading the auxiliary metal compound comprises: heating zinc nitrate, lanthanum nitrate or cerium nitrate at 90-98° C. in water to make it liquid, placing the stepped pore anodized aluminum carrier in the above solution, immersing it at 90-98° C. for 1-4 hours, drying it naturally, and then calcining it at 400-550° C. for 4 hours; The method for loading copper compounds comprises: placing the calcined product in a copper nitrate solution with a concentration of 1.5 mol / L, immersing at 25° C. for 10-20 hours, and calcining at 400-550° C. for 4 hours after natural drying.

9. Use of the catalyst according to claim 6 in methanol steam reforming.

Citation Information

Patent Citations

  • Structured catalyst for producing hydrogen by reforming dimethyl ether steam as well as preparation method and application of structured catalyst

    CN106140169A

  • Composite catalyst for reforming hydrogen production from methanol vapor as well as preparation method and hydrogen production method

    CN108671927A

  • Catalyst for hydrogen production by methanol steam reforming and preparation method of catalyst

    CN109603834A

  • Hydrogen production catalyst as well as preparation method and application thereof

    CN112827483A

  • Preparation method of catalyst for hydrogen production by methanol steam reforming as well as product and application thereof

    CN112588279A